You May Have My Help but Not Necessarily My Care: The Effect of Social Class and Empathy on Prosociality - Jiménez-Moya, Gloria; Luengo Kanacri, Bernadette Paula; Cumsille, Patricio; Martínez, M. Loreto; Berger, Christian (Frontiers in Psychology, 2021)
Previous research has focused on the relation between social class and prosocial behavior. However, this relation is yet unclear. In this work, we shed light on this issue by considering the effect of the level of empathy and the social class of the recipient of help on two types of prosociality, namely helping and caring. In one experimental study we found that for high-class participants empathy had a positive effect on helping, regardless of the recipient's social class. However, empathy had no effect for low-class participants. When it comes to caring, empathy had a positive effect for both high and low-class participants, but only when the recipient of help belonged to the same social class. This highlights that empathy by itself is not sufficient to promote cooperative relations and that the social class of the recipient of help should be taken into account to shed light on this issue.